2020
DOI: 10.1016/j.niox.2020.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Influence of muscle oxygenation and nitrate-rich beetroot juice supplementation on O2 uptake kinetics and exercise tolerance

Abstract: We tested the hypothesis that acute supplementation with nitrate (NO3 -)-rich beetroot juice (BR) would improve quadriceps muscle oxygenation, pulmonary oxygen uptake ( O2) kinetics and exercise tolerance (Tlim) in normoxia and that these improvements would be augmented in hypoxia and attenuated in hyperoxia. In a randomized, double-blind, cross-over study, ten healthy males completed two-step cycle tests to Tlim following acute consumption of 210 mL BR (18.6 mmol NO3 -) and NO3 --depleted beetroot juice place… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 65 publications
1
8
2
Order By: Relevance
“…Plasma [NO 2 − ] was lowered by a similar magnitude postexercise compared with preexercise across the BR trials in normoxia and both hypoxic doses, with postexercise plasma [NO 2 − ] higher in the BR compared with the PLA trials. These observations are consistent with previous reports of a similar decline in plasma [NO 2 − ] during exhaustive exercise in normoxia and hypoxia (Cocksedge et al, 2020;Kelly et al, 2014) and suggest that circulating NO 2 − is used as a substrate and reduced to bioactive NO. Interestingly, the rate of decline in plasma [NO 2 − ] during the exhaustive high-intensity intermittent running protocol was similar after BR supplementation in the 0 and 1,200-m conditions but was greater than both these conditions in 2,400 m. This novel observation suggests that the greater plasma NO 2 − pool after BR supplementation is only used more rapidly during exhaustive intermittent exercise after moderate, but not low, hypoxic conditions compared with normoxia.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Plasma [NO 2 − ] was lowered by a similar magnitude postexercise compared with preexercise across the BR trials in normoxia and both hypoxic doses, with postexercise plasma [NO 2 − ] higher in the BR compared with the PLA trials. These observations are consistent with previous reports of a similar decline in plasma [NO 2 − ] during exhaustive exercise in normoxia and hypoxia (Cocksedge et al, 2020;Kelly et al, 2014) and suggest that circulating NO 2 − is used as a substrate and reduced to bioactive NO. Interestingly, the rate of decline in plasma [NO 2 − ] during the exhaustive high-intensity intermittent running protocol was similar after BR supplementation in the 0 and 1,200-m conditions but was greater than both these conditions in 2,400 m. This novel observation suggests that the greater plasma NO 2 − pool after BR supplementation is only used more rapidly during exhaustive intermittent exercise after moderate, but not low, hypoxic conditions compared with normoxia.…”
Section: Discussionsupporting
confidence: 93%
“…Since the reduction of NO 2 − to NO is enhanced as PO 2 declines (Jones et al, 2016), there has been great interest in the ergogenic potential of NO 3 − supplementation in hypoxia. In recreationally active or moderately trained individuals, NO 3 − supplementation has been reported to improve continuous endurance performance in normobaric hypoxia (Cocksedge et al, 2020;Kelly et al, 2014;Masschelein et al, 2012;Muggeridge et al, 2014), with greater improvements in hypoxia compared with normoxia (Cocksedge et al, 2020;Kelly et al, 2014). Although the effects of NO 3 − supplementation on continuous endurance performance in normobaric hypoxia in trained individuals are less clear (Arnold et al, 2015;Bourdillon et al, 2015;MacLeod et al, 2015;Nybäck et al, 2017;Rokkedal-Lausch et al, 2019), there is evidence to suggest that, in contrast to normoxia (Porcelli et al, 2015), improved performance with NO 3 − supplementation in hypoxia is not linked to aerobic fitness (Shannon et al, 2016).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, NO 3 − has also been shown to be ineffective at influencing muscle oxygenation [66,[77][78][79]. In hypoxic states, NO 3 − supplementation has been shown to preserve muscle oxygenation [80,81] but also shown to have no effect [82]. Therefore, our data suggest that improved bench press RTF after acute NO 3 − supplementation is not linked to altered pectoralis major tissue oxygenation.…”
Section: Influence Of No 3 − Supplementation On Muscle Oxygenationmentioning
confidence: 61%
“…Previous reports show that changes in NO levels influence muscle PO 2 mv during transitions of metabolic demand, suggesting that augmented NO-mediated function could, at least in part, enhance muscle microvascular oxygenation in trainers [35]. More recently, Cocksedge et al [36] found that beetroot juice (supplements rich of NO 3 − ) has no effect on TOI, VO 2 kinetics, and exercise tolerance when severe intensity exercise (similar to our results; 3.49 vs. 3.46 L/min) occurred in normoxia with respect to hypoxia. The authors concluded that NO supplementation during severe exercise is related to the level of muscle deoxygenation sustained during such exercise intensity.…”
Section: Discussionmentioning
confidence: 96%